Possibilities of Solution of an Automobile Designing and Operation in Relation to the Environment - Vladimir Hlavna; Rastislav Istenik (Communications - Scientific letters of the University of Zilina, 2003)
The impact on the environment caused by operation of automobiles is obvious. Although production of emissions in steady-state operations is more or less successfully solved, unsteady operational modes result in a substantially greater impact on the environment. They are, in particular, an engine start and an automobile start up. The article deals with an analysis of an automobile start up and offers some ways of reducing the impact on the environment during the start up.